21f08-23 - Å ÅÓÖ ÌÀ ¾½¸ Ü ÑÔР׺ x2 2x−1...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Å ÅÓÖ ÌÀ ¾½¸ Ü ÑÔР׺ x2 +2x−1 º x3 −3x2 +2 Ü ÑÔÐ ½º ÓÑÔÙØ limx→3 Ü ÑÔÐ ¾º ÓÑÔÙØ limx→−1 ÈÖÓÓ º ÌÓ Ö¸ Û Ö ÐÐÝ √ x3 + 2x + 7º ÓÒ³Ø Ú Ø Ø x→−1 = lim x→−1 Ü ÑÔÐ ¿º ÓÑÔÙØ ¾º¾º Ä Ñ Ø Ì ×ÓÑ Ì ÖØ limx→9 ÓÖ Ñ׺ Ì × ×¸ ÙØ Û x3 + 2x + 7 lim Ò ÖÙ × ÑÔÐÝ Ø Ø¸ × Ò x3 + 2x + 7, x→−1 limx→−1 x3 + 2x + 7 = (−1)3 + 2(−1) + 7 = 4¸ Ò ÑØ x3 + 2x + 7 lim x→−1 Ø ÓÖÝ ØÓ Ð 2 lim x3 + 2x + 7 = Ó Äĸ ¾¼¼ Ø Ò limx→−1 √ x3 + 2x + 7 = 2º x2 −81 √ º x −3 ØÛÓ Ö ×ÙÐØ× Ñ Ý × ÑÖ Ø Ö Ó Ú ÓÙ׸ ÙØ Ø Ý Û ÐÐ ÐÔ Ñ × Ò× Ö Ò ×ØÝ Ð Ñ Ø׺ ÓÖ Ñ ½º Á Ò f (x) ≤ g(x) ÓÖ ÐÐ x Ò Ò ÓÔ Ò ÒØ ÖÚ Ð Ø Ø ÓÒØ Ò× a ´ Ü ÔØ ÔÓ×× ÐÝ Ø a Ø× Ð ¸ lim f (x) ≤ lim g(x). x→ a Ì ÓÖ Ñ ¾º Ì ´ Ü ÔØ ÔÓ×× ÐÝ ËÕÙ Ø Þ Ì ÓÖ Ñ℄ x→ a Á f (x) ≤ g(x) ≤ h(x) Ò Ò ÓÔ Ò ÒØ ÖÚ Ð Ø a Ø× Ð ¸ Ò lim f (x) = L = lim h(x), Ø x→ a Ò x→ a lim g(x) = L. x→ a Ü ÑÔÐ º Ë ÓÛ Ø Ø lim x sin x→ 0 ¹Ñ Ð Ö ×× Ú º Ó Ò×ÓÒÐ º Ù ½ 1 x =0 Ø ÓÒØ Ò× a ...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online